Experimental and numerical study of a photovoltaic/thermal system cooled by metal oxide nanofluids - Mohammed Alktranee; Qudama Al-Yasiri; Mohammed Ahmed Shehab; Péter Bencs; Zoltán Németh; Klara Hernadi (Alexandria Engineering Journal, 2024)
Photovoltaic modules are impacted by overheating, which degrades their conversion efficiency and shortens their lifespan. This work attempts to study the cooling potential for a hybrid photovoltaic/thermal (PV/T) system by employing CuO and Fe2O3 nanofluids with 0.2% and 0.3% volume fractions (φ), circulated in a heat exchanger attached at the rear side of the PV module to lower the temperature of the PV cells and improve its energy and exergy efficiencies. Consequently, a 2D numerical model was analysed given the energy balance across the PV/T system layers, which is evaluated in line with measured experimental data. The results indicate that the successfully synthesised nanomaterials could improve the performance of the nanofluids and increase the heat exchange between PV/T system layers, reducing the PV cells’ temperature by 23.49% and 34.58% when cooling by CuO and Fe2O3 nanofluids at φ=0.3%. Compared to the uncooled PV module, the electrical efficiency has increased by 9.21% and 10.30%, while thermal efficiency increased by 38.9% and 43.3% under cooling with CuO and Fe2O3 nanofluids, respectively. Thereby, the exergy destruction (exergy losses) and entropy generation have decreased by about 26% and 68% when cooling with Fe2O3 nanofluid, which improved the exergy efficiency by 13% more than CuO nanofluid.